Coaches Quality as Predictor of Sports Development in Edo State, Nigeria, West Africa - Awoma, Christopher .I. (Advances in Social Sciences Research Journal, 2014)
The study examined if quality of coaches is a predictor of Sports Development in Edo State, Nigeria. The study examined how quality of coaches would be a predictor of sports development in Edo State, Nigeria. The ex post – factor design was adopted for the study and the main research instrument used was a modified closed ended Likert type of questionnaire which was validated. The reliability of the instrument was employed using crombach alpha to determine the internal consistency of the questionnaire and 0.84 was obtained. The data was analyzed using regression statistical analysis set at 0.05 alpha levels. The findings was that, quality of coaches significantly predict sports development in Edo State, Nigeria (B=0.294, T=3.026, P<0.05). The null hypothesis is therefore rejected. Based on the findings, it was recommended that, Government, through her policies should ensure that before anybody becomes a coach, he or she should receive a formal training in coaching and equally ensure that, the coach must have extensive knowledge of the human physiology, growth and development.